Effect of Steel Fibres And Wire Mesh Reinforcement on Flexural Strength and Strain Energy Steel-Epoxy-Aluminium Composite Laminates / W. N. M. Jamil ...[et al.] - M. Jamil, W. N.; Sajuri, Z.; Aripin, M. A.; Abdullah, S.; Omar, M. Z.; Abdullah, M.F.; H. Zamri, W. F. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
This paper evaluates the effect of reinforcement materials on the flexural strength and strain energy in metal laminates under bending tests. Traditionally, high hardness monolithic steel has been utilised in lightweight armoured vehicles. In order to increase the performance of the armoured plates, their weight is reduced by incorporating adhesive bonding metal laminates technology. Simultaneously, the application of metallic fibres in construction is also being developed for the same purpose. Therefore the incorporation of metallic fibres in adhesive layer can reduce the weight and increase the strength of armoured panels. It is important to assess and predict the flexural strength and strain energy in the metal laminated armour. The effects of steel fibres and stainless steel mesh were investigated through flexural tests. The flexural strength was assessed by a three-point bending test using a universal testing machine. The strain energy was measured from the stress-strain curve using the data from the bending test. From the results, the steel fibre-reinforced and wire mesh-reinforced composite laminates exhibited higher flexural strength compared to non-reinforced composite laminate by 10% and 9%, respectively. Further, steel fibre-reinforced and wire mesh-reinforced composite laminates had higher strain energy at 23% and 31% compared to non-reinforced composite laminate, respectively. Cracks occurred at the back layer of the aluminium alloy and propagated vertically through the aluminium and adhesive layer and stopped at the steel layer. This is due to the higher strength and ductility of the steel in withstanding the load. Reinforcement with steel fibres and wire mesh enabled the metal laminate to bear higher load, while decreasing the damage and delamination due to its higher strength, strain energy and ductility compared to the non-reinforced composite laminate. The reinforcement materials have the potential to produce tough adhesive-bonded metal laminates for ballistic impact applications.